(3OZd GdYjfs - (3CHh RcQjGA jhMfG Hf eGShjI GdHZOGOj,J (B243 (3g` s ((3YHO GdQMef Hf EHQGgje Hf SGde Hf YeGQ GdCfUGQi GdebOSi GdeJWHH s)
(3ChdgG (B:s
(3ai eGFjI GdYjf hcjajJgG hJQcjHgG hYOO QWhHJgG hMLegG hYVdJgG hYUHJgG hCSeGFgG hefaYI cd hGMO efgG hef Cjf EHJOGFgG hEdi Cjf EfJgGFgG hLejY GdCOhGA GdYGQVI s
(3BNQgG (B:s
(3TjGa CUaQ JCNP fMGS eMQb hRf YTQI OQGge SHYI OQGge SfHd hRYaQGf Je GdcJGH ai JQcjH WHbGJ GdYjf hYdGLgG djhMfG Hf eGShjg GdeJWHH s
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs